Heritage building information modelling for implementing UNESCO procedures : challenges, potentialities, and issues - Baik, Ahmad (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The main aim of this book is to develop and explore the value of new innovative digital content to help satisfy the UNESCO's World Heritage nomination file requirements"--
OCLC-licensed vendor bibliographic record.
Keywords: Historic preservation -- Data processing; Historic sites -- Conservation and restoration -- Data processing; Building information modeling; ARCHITECTURE / Historic Preservation; TECHNOLOGY / Imaging Systems